Advanced Chemical Reduction of Reduced Graphene Oxide and Its Photocatalytic Activity in Degrading Reactive Black 5 - Wong, C.P.P.; Lai, Chin Wei; Lee, K.M.; Hamid, Sharifah Bee Abd (MDPI, 2015)
Textile industries consume large volumes of water for dye processing, leading to undesirable toxic dyes in water bodies. Dyestuffs are harmful to human health and aquatic life, and such illnesses as cholera, dysentery, hepatitis A, and hinder the photosynthetic activity of aquatic plants. To overcome this environmental problem, the advanced oxidation process is a promising technique to mineralize a wide range of dyes in water systems. In this work, reduced graphene oxide (rGO) was prepared via an advanced chemical reduction route, and its photocatalytic activity was tested by photodegrading Reactive Black 5 (RB5) dye in aqueous solution. rGO was synthesized by dispersing the graphite oxide into the water to form a graphene oxide (GO) solution followed by the addition of hydrazine. Graphite oxide was prepared using a modified Hummers' method by using potassium permanganate and concentrated sulphuric acid. The resulted rGO nanoparticles were characterized using ultraviolet-visible spectrophotometry (UV-Vis), X-ray powder diffraction (XRD), Raman, and Scanning Electron Microscopy (SEM) to further investigate their chemical properties. A characteristic peak of rGO-48 h (275 cm-1) was observed in the UV spectrum. Further, the appearance of a broad peak (002), centred at 2θ = 24.1°, in XRD showing that graphene oxide was reduced to rGO. Based on our results, it was found that the resulted rGO-48 h nanoparticles achieved 49% photodecolorization of RB5 under UV irradiation at pH 3 in 60 min. This was attributed to the high and efficient electron transport behaviors of rGO between aromatic regions of rGO and RB5 molecules.